Acoustic behavior of composites with gradient impedance. (August 2020) - Feng, Yiwen; Qiao, Jing; Li, Longqiu
Abstract: Conventional acoustic materials with uniform media which are of fixed impedance and density are unable to satisfy the requirements of the development of modern acoustic technology in volume, weight, pressure resistance and stealth performance. In this paper, composite structures with different gradient impedances are proposed. The influence of impedance gradient forms and discrete layering methods on acoustic performance is investigated numerically and experimentally. It is found that the gradient structure with exponential form improves absorbing performance in low frequency best among all these forms studied in terms of absorption coefficient and reflection coefficient. The curvature of the exponential curves shows the greatest effects on the position of the first absorption peak and the corresponding absorption coefficient. Better acoustic properties can be obtained in the case when adopting the equivalent layering method by thickness than that of the method equally layering by impedance. These findings provide useful guidance for application of underwater acoustic impedance gradient medium in engineering, especially for designing customized anechoic coating. Graphical abstract: Unlabelled Image Highlights: Composite structures with different gradient impedances are proposed. The gradient structure with exponential form shows the best acoustic properties. The impedance gradient forms and discrete layering methods show great effect on acoustic properties.